Understanding Chinese EFL learners’ anxiety in second language writing for the sustainable development of writing skills - Yu, Yue; Zhou, Dandan (Frontiers in Psychology, 2022)
To add to the currently limited research on the degree of cultural uniqueness of Chinese EFL learners’ anxiety and the multidimensional nature of second language writing anxiety (SLWA), the present qualitative study used think-aloud protocol and interview to examine Chinese EFL learners’ three dimensions of SLWA and the related variables, so as to probe into this problem that could pose an obstacle to sustainable second language writing. Findings showed that Chinese EFL learners experienced much Cognitive Anxiety, but relatively little Avoidance Behavior. Learner-internal, teacher-related, and human-external variables interacted with SLWA in a dynamic way. To a certain degree, Chinese EFL learners showcased uniqueness in some aspects of SLWA, under cultural influences, regarding ethnic culture, local culture, academic culture, and disciplinary culture.